(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Deep brain stimulation (DBS) is a minimally invasive technique in which electrodes are implanted in deep areas of the brain to treat neurological pathologies. It is recommended for Parkinson’s disease, obsessive-compulsive disorder, essential tremors, epilepsy and dystonia. The main symptoms of Parkinson’s disease, such as bradykinesia, tremors, repetitive stiffness and weakness in arms and legs, are greatly reduced after the deep brain stimulation. For Parkinson’s patients who are unresponsive to medication, deep brain stimulation is a gold standard. The immediate effectiveness in reducing the symptoms, the minimally invasive procedure and the fewer postoperative complications are the highlights of this specific surgical procedure, which make it the best choice for the surgeon as well as for the patient. The postoperative period is short, and the patient recovers within weeks and comes to routine within a month. This surgery is performed frequently for patients with stage 4 Parkinson’s disease in the department of Neurosurgery and Neuro-rehabilitation at Samarkand State Medical University, Uzbekistan. A total sample size of 68 reports in the year 2024, which consisted of 24 consecutively referred patients for DBS were used to obtain data for examination of age, gender and subtype. The results of our study showed that DBS was conducted more in the elderly and male population. This article also explores the clinical outcomes and limitations of DBS in patients with Parkinson’s disease, evaluating the effectiveness, complications and potential risks to be considered. Although DBS seem to be the safest solution for Parkinson’s disease, further advancements are still required to enhance therapeutic precision and minimize adverse effects.